ETIKA BERSOSIAL MEDIA DALAM PERSPEKTIF AL-QUR’AN - Harliza Lahfa Ma’ajidah; Isa Anshori; Budi Haryanto (PAI RAFAH, 2023)
The development of technology and information has direct consequences on human habits in utilizing them for various daily activities. This reliance on information technology has become so significant that there is even a sense of discomfort experienced when it is absent, including within Muslim communities. Social media is one of the most advanced technologies that is highly sought after and extensively utilized across all levels of society. It serves various purposes, such as facilitating connections between friends, providing access to information and communication, enabling transactions and business activities, fostering new relationships, and much more. However, social media can also have negative consequences when users fail to respond to it properly and wisely. Examples of these consequences include manipulation, offense, disputes, and conflicts. This study employs a qualitative research method with a phenomenological approach. The findings of the study demonstrate that the utilization of social media is effective and positive when users adhere to the various ethics outlined in the Al-Qur'an. The Al-Qur'an emphasizes that the use of social media prohibits the dissemination of fake news or hoaxes. It stresses the importance of validating information before sharing it with others or receiving it. Additionally, it encourages individuals to refrain from criticizing others and to maintain the use of respectful and appropriate language when interacting with fellow human beings.